Pembentukan Aliansi Keamanan Iran-Rusia - Widian, Rizky; DR, Muhammad Rusyidi; Widian, Willy (Parahyangan Center for International Studies, 2018)
Russia and Iran are countries with high cooperative relations. However, in recent years, Russia-Iran relations have declined. This is due to the Iranian nuclear issue, which at the time Russia was present as a party that gives UN sanctions to Iran. Despite of this fact, by 2015, Russia and Iran signed a military cooperation agreement signaling the establishment of a Russian-Iranian security alliance. The author sees that there is a puzzle, namely the establishment of the security alliance even though Russia has helped to put pressure on Iran. Furthermore, the authors argue that there are several reasons or factors for the formation of the Russian-Iranian security alliance. In explaining this, this writing will borrow the theory Balance of Threat proposed by Stephen M. Walt. Thus, this paper will be divided into several parts. First, will be presented on the background of the problem and the theoretical framework to be used. Then, it will be explained about the discussion of factors that encourage the formation of the Russian-Iranian security alliance. In the last section will be closed with a conclusion.